Burn baby burn - Medina, Meg 1963- (Candlewick Press, 2016)
It is the summer of 1977, and New York is suffering under a heat wave, a massive blackout, and a killer named the Son of Sam, while seventeen-year-old Cuban American Nora Lopez wants to escape her increasingly violent younger brother and worries about college applications and paying rent to spend her days working at the deli with the cute new Colombian boy and her nights at the disco dancing with her best friend Kathleen